The structure and function of soil archaea across biomes - Starke, Robert; Siles, José A; Fernandes, Maysa Lima Parente; Schallert, Kay; Benndorf, Dirk; Plaza, Cesar; Jehmlich, Nico; Delgado-Baquerizo, Manuel; Bastida, Felipe (Journal of proteomics, 2021)
We lack a predictive understanding of the environmental drivers determining the structure and function of archaeal communities as well as the proteome associated with these important soil organisms. Here, we characterized the structure (by 16S rRNA gene sequencing) and function (by metaproteomics) of archaea from 32 soil samples across terrestrial ecosystems with contrasting climate and vegetation types. Our multi-"omics" approach unveiled that genes from Nitrosophaerales and Thermoplasmata dominated soils collected from four continents, and that archaea comprise 2.3 ± 0.3% of microbial proteins in these soils. Aridity positively correlated with the proportion of Nitrosophaerales genes and the number of archaeal proteins. The interaction of climate x vegetation shaped the functional profile of the archaeal community. Our study provides novel insights into the structure and function of soil archaea across climates, and highlights that these communities may be influenced by increasing global aridity.
Keywords: Metaproteomics; Vegetation; RNA, Ribosomal, 16S; RNA ribozomální 16S; Archaea; půda; Soil; Soil Microbiology; 16S rRNA gene amplicon sequencing; Climate; půdní mikrobiologie; ekosystém; Ecosystem